Chemotherapy dose per kilogram lean body mass increased dose-limiting toxicity event in male head and neck cancer with taxane and platinum-based induction therapy - Chuan-Jen Hung; Bor-Hwang Kang; Keng-Ming Chang; Ying-Ying Kang; Chun-Hao Yin; Ching-Chih Lee (BMC Cancer, 2022)
Abstract Background This study aimed to determine whether drug doses per kilogram of lean body mass (LBM) were associated with dose-limiting toxicity (DLT) events in head and neck cancer (HNC) patients. Methods This retrospective cohort study included 179 HNC patients who underwent induction chemotherapy (IC) at a medical center from May 1, 2014, to May 31, 2021. HNC patients’ characteristics, tumor factors, IC regimen and dose, laboratory data, and body composition factors, including lean body mass (LBM) and skeletal muscle index (SMI), derived from CT, MRI, or PET scan images and drug dose per kilogram LBM were recorded. Dose-limiting toxicity (DLT) events were regarded as the primary outcome. Multivariate logistic regression was used to establish a novel risk score for DLT events by the abovementioned variables. The above-mentioned risk score was validated in another cohort. Results The overall DLT events during the first cycle of IC for 179 HNC patients was 24%. After stratifying by gender, docetaxel per kilogram LBM > 2.52 mg/kg (adjusted odds ratio [aOR]: 3.18; 95% confidence interval [CI], 1.25–8.09), pre-treatment glutamic pyruvic transaminase (GPT) > 40 U/L (aOR, 2.61; 95% CI, 1.03–6.64), and history of chronic liver diseases (aOR, 3.98; 95% CI, 1.03–15.46) were significant variables in male HNC patients. The DLT events risk was categorized by summation of the above-mentioned risk factors for male HNC patients. Three risk groups were stratified by overall event of 17.6%, 25.8%, and 75%. The above-mentioned risk score had an acceptable discriminatory ability in another validation cohort. Conclusions Among male HNC patients treated with IC, docetaxel per kilogram LBM more than 2.52 mg/kg, pre-treatment GPT > 40 U/L, and history of chronic liver disease were significant risk factors for DLT events. Identifying high-risk patients could help physicians prevent severe/fatal complications among HNC patients undergoing IC, especially for the male individuals.